Mechanisms of Particles in Sensitization, Effector Function and Therapy of Allergic Disease - Joubert, Isabella Anna; Geppert, Mark; Johnson, Litty; Mills-Goodlet, Robert; Michelini, Sara; Korotchenko, Evgeniia; Duschl, Albert; Weiss, Richard; Horejs-Höck, Jutta; Himly, Martin (Frontiers in Immunology, 2020)
Humans have always been in contact with natural airborne particles from many sources including biologic particulate matter (PM) which can exhibit allergenic properties. With industrialization, anthropogenic and combustion-derived particles have become a major fraction. Currently, an ever-growing number of diverse and innovative materials containing engineered nanoparticles (NPs) are being developed with great expectations in technology and medicine. Nanomaterials have entered everyday products including cosmetics, textiles, electronics, sports equipment, as well as food and food packaging. As part of natural evolution humans have adapted to the exposure to particulate matter, aiming to protect the individual’s integrity and health. At the respiratory barrier, complications can arise, when allergic sensitization and pulmonary diseases occur in response to particle exposure. Particulate matter in the form of plant pollen, dust mites feces, animal dander, but also aerosols arising from industrial processes in occupational settings including diverse mixtures thereof can exert such effects. This review article gives an overview of the allergic immune response and addresses specifically the mechanisms of particulates in the context of allergic sensitization, effector function and therapy. In regard of the first theme (i), an overview on exposure to particulates and the functionalities of the relevant immune cells involved in allergic sensitization as well as their interactions in innate and adaptive responses are described. As relevant for human disease, we aim to outline (ii) the potential effector mechanisms that lead to the aggravation of an ongoing immune deviation (such as asthma, chronic obstructive pulmonary disease, etc.) by inhaled particulates, including NPs. Even though adverse effects can be exerted by (nano)particles, leading to allergic sensitization and the exacerbation of allergic symptoms, promising potential has been shown for their use in (iii) therapeutic approaches of allergic disease, for example as adjuvants. Hence, allergen-specific immunotherapy (AIT) is introduced and the role of adjuvants such as alum as well as the current understanding of their mechanisms of action is reviewed. Finally, future prospects of nanomedicines in allergy treatment are described, which involve modern platform technologies combining immunomodulatory effects at several (immuno-)functional levels.